FILM AS MEDIA TO TEACH WRITING AT THE ELEVENTH GRADE STUDENTS OF SMA NEGERI TUGUMULYO - Kalila, Faranisa Zaibah (Journal of Language, Literature and Teaching, 2021)
This study was entitled film as media to teach writing at the eleventh grade students of SMA Negeri Tugumulyo. The purpose of conducting this study was to examine whether this is a significant or not film as media to teach writing at the eleventh grade students of SMA Negeri Tugumulyo. This study used quantitative study, which focused on writing achievement at the eleventh grade students of SMA Negeri Tugumulyo. The writer formulated two hypotheses; there were null hypothesis (Ho) and the alternative hypothesis (Ha). There were 352 students from nine classes as the population of this study. The sample was taken through cluster random sampling was the class XI IA.2 which consists of 37 students. In this case, the writer collected the data by using writing test. Then, the techniques for analyzing the data were the students’ individual score and Match T-test to find out the tobtained. Based on the findings, the result showed that tobtained was 6.38, it was higherthan ttable was 1.697 (tobtained bigger ttable), it could be concluded that the Null Hypothesis (Ha) significantly effective film as media to teach writing at the eleventh grade students of SMA Negeri Tugumulyo.